CONFERENCING: AN INTERACTIVE STRATEGY IN TEACHING ACADEMIC WRITING - Wienny Ardriyati; Sri Murtiningsih (Soegijapranata Catholic University, 2005)
Writing plays an essential role in our personal and professional lives. It becomes one of the important components in learning and teaching English for Academic Purposes (EAP). This article suggests the benefits of teaching writing by using conferencing technique is effective for communicative purposes in an interactive way. In this context, the teaching of writing for the students in their widely varying personal needs and goals can be in the form of conferencing, a short meeting between the students and the teacher. Teaching writing through conferencing gives some benefits, for instance, it enables the teacher to modify and adapt instructional methods and approaches according to the students needs. From this perspective, writing implying the successful transmission of ideas from the writer to a reader through a text, this exchange of information becomes a powerful means to encourage the development this language skill.